Microsoft office 2003 - O'Leary, Timothy J. (McGraw-Hill Technology Education, 2003)
The goal of the O'Leary Series is to give students a basic understanding of computing concepts and to build the skills necessary to ensure that an "O'Leary" student has an advantage in whatever career they choose. The text design emphasizes step-by-step instructions with full screen captures that illustrate the results of each step performed. This method allows students to learn at their own pace. Each Tutorial (chapter) combines conceptual coverage with detailed software-specific instructions. A running case that is featured in each tutorial highlights the real-world applications of each software program and leads students step-by-step from problem to solution